Resepsi Khalayak Gen Z Berbasis Gender Tentang Skincare Lokal Overclaim Dalam Tayangan Youtube Denny Sumargo: Terlalu Berani - Zanah, Saniyati Raudatul; Mustiawan, Mustiawan; Putra, Gilang Kumari (Jurnal Penelitian Dan Pengkajian Ilmiah Sosial Budaya, 2025)
Reception to the Denny Sumargo YouTube broadcast episode is too bold, raising the issue of local skincare that makes excessive claims on skincare product ingredients. The increasing use of skincare products, so that some have felt the side effects of overclaimed skincare. As felt by a TikToker named Tya from Kalimantan who experienced skin cancer such as black spots. Gen Z is the most active group in consuming skincare products. This study aims to understand how the Gen Z audience in Jakarta actively receives and interprets messages on Denny Sumargo's YouTube broadcast. The study used a qualitative method with a reception analysis approach through the encoding and decoding model from Stuart Hall. Informants were selected in a planned manner from the South Jakarta Karang Taruna administrators, male and female. The results showed that informants did not receive messages passively. Several informants showed dominant acceptance, namely agreeing with the contents of the message and supporting criticism of the practice of overclaim. Other informants showed negotiation and opposition acceptance, namely questioning the motives behind the broadcast and assessing that the content was subjective.